Study of Eriophyoid Mites (Acari: Eriophyoidea) of Different Districts from Less Explored Places of South Bengal, India - Som, Dipak Kumar; Maji, Shubhajit; Bhadra, Sayan; Parveen, Ghajala; Khatun, Safiyana; Patra, Swarnali; Sur, Surajit (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study was conducted across various lesser known places of Southern part West Bengal from January 2024 to July 2024. This area appears to have been previously unexplored in terms of eriophyoid mite diversity. A total of 60 Eriophyoid mite species, belonging to 29 genera and 2 families were recorded, with families: Eriophyidae accounting for 85% and Diptilomiopidae for 15%. Simpson’s index and the Shannon-Wiener diversity index were calculated to assess the mite community in different study areas. These mites were found on a wide variety of host plants, such as Anthocephalus kadamba, Litchi litchi, Mangifera indica, and Ficus spp., reflecting complex ecological relationships. These mites were exclusively vagrant in nature, and their presence often led to plant damage, including galls, leaf curling, and other deformities, highlighting their significant impact on plant health.